Use of Cracker Residue in the Diet of Dairy Heifers: Impacts on Animal Health, Ruminal Fatty Acids Profile, Digestibility, Weight Gain, and Economic Viability - Vitt M.G.D.* (2024)
© 2024 by the authors.This study determined whether the isomeric or isoenergetic/isoproteic substitution of corn in the diet of Jersey heifers in the rearing phase with cracker residue would impair growth and health, as well as reducing production costs. Fourteen Jersey females in the growth phase were used, separated into two treatments with seven animals in each lot in collective pens. The experiment used 7-month-old animals (169.8 ± 2.89 kg) and lasted for four months. In Experiment I, the animals were divided into two groups: treatment, with the partial replacement of 40% corn with cracker residue, and control, in which the animals consumed the same diet with 100% corn (isometric diet kg for kg). In Experiment II, the animals with a body weight of 200.2 ± 3.85 kg were divided into two groups: Treatment, replacing 100% of the corn with cracker residue, and control, in which the animals consumed an isoprotein and isoenergetic diet but with 100% of the corn in the formulation. The diet consisted of concentrate, Tifton 85 hay, and corn silage, supplied twice a day individually, with animals contained in their feeders by kennels. There was water ad libitum in the bay. Biweekly weighing and monthly blood analysis were performed, totaling four collections per part for hematologic evaluation, carbohydrate, lipid, and protein metabolism variables. At the end of each experiment, ruminal fluid was collected to measure the volatile fatty acid profile, and feces were collected to determine the apparent digestibility coefficient (ADC). Experiments I and II showed no effect of treatment on body weight, weight gain, average daily weight gain, feed intake, and feed efficiency. There was no effect of treatment on leukocyte, erythrocyte, lymphocyte, neutrophil, monocyte, and eosinophil counts, hematocrit, and hemoglobin concentration (p > 0.05). Experiment I showed a difference between groups for the variables albumin, globulin, total proteins, cholesterol, glucose, and urea, which did not happen in Experiment II. In both experiments, a higher ADC of nutrients was found in the treatment group which had cracker residue (p > 0.05). The concentration of volatile fatty acids in Experiment I was higher in the control group, unlike in Experiment II, where the highest concentration was in the treatment group (p > 0.05). Because experiment I had an isometric substitution, the diets had different bromatological composition, which is the probable cause of the difference between groups; this did not happen in experiment II, in which the diets consumed by the animals was isoproteic and isoenergetic. Based on these data we conclude that the substitution of cracker residue in an isomeric or isoenergetic/isoproteic form does not negatively affect weight gain and animal health, as well as reduces the cost of the concentrate, consequently reducing the cost of production of these animals.